2014
DOI: 10.3329/bjb.v42i2.18038
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant activity of essential oils of three endemic medicinal plants of Iran

Abstract: Hydro-distillated essential oils (EO) antioxidant activity of three endemic medicinal plants of Iran namely, Heracleum lasiopetalum Boiss., Kelussia odoratissima Mozaff., and Ferulago angulata (Schlecht.) Boiss were studied. The results indicated that the major components of the EOs were 2-ethylhexyl acetate (34.5%), n-octanol (6.5%), and hexanol (5.1%) for H. lasiopetalum fruits; Z-β-ocimene (20.5), α-pinene (11.6%), and α-phellandrene (9.3) for F. angulata aerial parts; α-pinene (20.1%), 1,8-cineole (18.2%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Although differences can be observed in the percentage distribution, in conformity with our findings (Z)-β-ocimene and α-pinene were dominant oil compounds in an earlier investigation. [32] Moreover, regarding the previously reported contents of the aerial parts, oil of the plant consists of monoterpenes as a major constituent [9] which is in conformity with our results. On the other hand, our findings differ from those reported in some investigations, in which other components such as α-phellandrene and β-phellandrene [3,9] , suberosin, spathulenol, trans-β-caryophyllene, arcurcumene, and bicyclogermacrene [6] , α-pinene, limonene, β-myrcene, and fenchyl acetate [9] were the major compounds.…”
Section: Oil Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…Although differences can be observed in the percentage distribution, in conformity with our findings (Z)-β-ocimene and α-pinene were dominant oil compounds in an earlier investigation. [32] Moreover, regarding the previously reported contents of the aerial parts, oil of the plant consists of monoterpenes as a major constituent [9] which is in conformity with our results. On the other hand, our findings differ from those reported in some investigations, in which other components such as α-phellandrene and β-phellandrene [3,9] , suberosin, spathulenol, trans-β-caryophyllene, arcurcumene, and bicyclogermacrene [6] , α-pinene, limonene, β-myrcene, and fenchyl acetate [9] were the major compounds.…”
Section: Oil Analysissupporting
confidence: 80%
“…[9,10,30] Chemical compounds and biological activity of some species from the genus Ferulago have been the subject of preceding studies. [8,9,14,17] The reports on the chemical compositions of the oils isolated from the aerial parts F. angulata are abundant [6,7,11,13,[30][31][32] as most of these investigations showed patterns of oil compositions similar to our present study. Although differences can be observed in the percentage distribution, in conformity with our findings (Z)-β-ocimene and α-pinene were dominant oil compounds in an earlier investigation.…”
Section: Oil Analysissupporting
confidence: 79%
“…F. angulata has already shown to have high antioxidant properties [14]. It has been reported that the hydroalcoholic extract of F. angulata can reduce serum levels of total cholesterol, triglycerides, and low-density lipoproteins (LDL) as well as inhibiting lipid peroxidation in Wistar rats [15].…”
Section: Introductionmentioning
confidence: 99%
“…The essential oils of F. sandrasica were also reported to have antibacterial and antioxidant activities with the emphasis that phenolic compounds may be responsible for the antioxidant activity . Moreover, F. angulata essential oil was determined to have antioxidant activities . In addition, it has been reported that Ferula assafoetida L. exhibited anxiolytic effects in rodents within the elevated plus‐maze model of anxiety .…”
Section: Introductionmentioning
confidence: 99%